الأداء الوظيفي في ضوء القدرات الإبداعية لدى العاملين بالأندية الرياضية بسلطنة عمان - جعفر، أمين محمود (جامعة الأسكندرية - كلية التربية الرياضية للبنين بأبوقير, 2016)
يهدف البحث إلى التعرف على الأداء الوظيفي في ضوء القدرات الإبداعية لدى العاملين بالأندية الرياضية بسلطنة عمان وتمثلت عينة الدراسة من أعضاء مجالس إدارة أندية "مسقط، السيب، عمان، أهلي سداب" وبلغ عددهم (31) عضو مجلس إدارة، وبعض العاملين بهذه الأندية وبلغ عددهم (45) عامل بالنادي واستخدم الاستبيان كأحد أدوات جمع البيانات وقام الباحث بإجراء دراسة استطلاعية بتاريخ 5/3 / 2015 لعينة قوامها (20) فردا اختيروا عشوائيا من المجتمع الأصلي وخارج عينة الدراسة وقد تم تطبيق الدراسة الأساسية في الفترة من 20/ 3/ 2015 إلى 18/ 5/ 2015 م وكانت أهم النتائج تتوفر لدى العاملين بالأندية الرياضية جميع القدرات الإبداعية بدرجة عالية وهي مرتبة كالتالي قبول المخاطرة، التحليل والربط، الاحتفاظ بالاتجاه أو تركيز الانتباه، المرونة الذهنية، القدرات المميزة للشخصية، الحساسية للمشكلات، الطلاقة الفكرية، وجود علاقة طردية بين القدرات الإبداعية "قدرات الشخصية المبدعة، الطلاقة الفكرية، المرونة الذهنية، الحساسية للمشكلات، الاحتفاظ بالاتجاه أو تركيز الانتباه، قبول المخاطرة، التحليل والربط "وبين مستوى الأداء الوظيفي لدى العاملين بالأندية الرياضية بسلطنة عمان.
The research aims to identify the functionality in light of the creative capabilities of workers sports clubs in the Sultanate of Oman, represented a sample study of members of boards of clubs, "Muscat, Seeb, Oman, Ahli management Sidab" and numbered (31) Member of the Board, and some of the staff of these clubs and numbered (45) factor the club and use the questionnaire as a data collection tools and the researcher conducted a prospective study on 05/03/2015 for a sample of 20 individuals randomly selected from the original community and outside the study sample has been applied to the basic study in the period from 20/03/2015 to 05/18/2015 AD and was the most important results among workers sports clubs all creative capabilities are available with a high degree are arranged as follows accept the risk, analysis and connectivity, keep the direction or focus of attention, mental flexibility, special personal capacity, sensitivity to problems, intellectual fluency, and a positive relationship between creative abilities "personal capabilities creative, intellectual fluency, mental flexibility, sensitivity to problems, keep the direction or focus of attention, accept the risk, analysis and linkage" between job performance and working with sports clubs in the Sultanate of Oman level.
Keywords: الإدارة الرياضية -- إدارة الموارد البشرية -- المؤسسات الرياضية -- سلطنة عمان